Relationship Between Central Obesity and Low Back Pain Complaints Among Housewives in Kampung Sawah Village, West Sumba - Dominggus R.K.U.W Pandango; Su Djie To Rante; Audrey Gracelia Riwu; Dwita Anastasia Deo (Jurnal Biologi Tropis, 2026)
Central obesity can increase mechanical stress and inflammation on the spine, which can lead to low back pain (LBP). Housewives have limited physical activity and repetitive domestic workloads that can exacerbate this risk. Objective to determine the relationship between central obesity and low back pain complaints among housewives in Kampung Sawah Village, West Sumba. Method: A cross-sectional analytical study of 101 housewives. Methods: The study used an observational analytical design with a cross-sectional approach. A total of 101 housewives were included as respondents. Central obesity was determined based on waist circumference measurements, while LBP complaints were assessed using a standardised questionnaire. The analysis of the relationship between variables was performed using the Chi-Square test. Results of the total respondents, 89 people (88.1%) were identified as having central obesity, and 67 of them reported complaints of LBP. The Chi-Square test showed a value of p=0.001, indicating a significant relationship between central obesity and complaints of low back pain. There is a significant relationship between central obesity and LBP complaints among housewives in Kampung Sawah Village, West Sumba. Prevention can be achieved through increased physical activity and education on ergonomic work posture.